Growth hormone (GH) activity is associated with increased serum oestradiol and reduced Anti‐Müllerian Hormone in healthy male volunteers treated with GH and a GH antagonist. (19th June 2013) - Andreassen, M.; Frystyk, J.; Faber, J.; Kristensen, L. Ø.; Juul, A.
Summary Growth hormone (GH) and insulin‐like growth factor I (IGF‐I) receptors are present on pituitary gonadotrophs and on testicular Leydig and Sertoli cells. Thus, the GH/IGF‐I system may modulate the pituitary‐gonadal axis in males. This is a randomized cross‐over study. Eight healthy male volunteers (mean age 35, range 29–46 years) were treated with GH for 3 weeks (1st week 0.01, 2nd week 0.02, 3rd week 0.03 mg/day/kg) or a GH receptor antagonist (Pegvisomant) (1st week 10, last 2 weeks 15 mg/day), separated by 8 weeks of washout. Before and after the two treatment periods, concentrations of luteinizing hormone (LH), follicle‐stimulating hormone, testosterone, oestradiol, sex hormone–binding globulin, inhibin B and Anti‐Müllerian Hormone (AMH) were measured. During GH treatment, IGF‐I increased [(median (IQR)] 166 (162–235) vs. 702 (572–875) μg/L, p < 0.001) together with oestradiol [(mean ± SD) 78 ± 23 vs. 111 ± 30 pm, p = 0.019], and the oestradiol/testosterone ratio (p = 0.003). By contrast, AMH (42 ± 14 vs. 32 ± 7 pm, p = 0.018), Inhibin B (211 (146–226) vs. 176 (129–204) ng/L, p = 0.059) and LH (3.8 ± 1.5 vs. 3.2 ± 1.2 U/L, p = 0.096) decreased. During pegvisomant treatment IGF‐I (204 (160–290) vs. 106 (97–157) μg/L, p = 0.001) and oestradiol (86 ± 28 vs. 79 ± 25 pm, p = 0.060) decreased. No significant changes or trends in the other reproductive hormones occurred during the two treatment regimens. GH/IGF‐I activity was positively associated with serum oestradiol, suggesting that GH/IGF‐I stimulates aromatase activity in vivo. As a novel observation, we found that high GH activity was associated with reduced levels of the Sertoli cell marker AMH. Further studies are needed to evaluate possible effects of GH on Sertoli cell function and/or spermatogenesis.